2019
DOI: 10.1093/jmammal/gyz163
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of moose in western North America

Abstract: Subspecies designations within temperate species’ ranges often reflect populations that were isolated by past continental glaciation, and glacial vicariance is believed to be a primary mechanism behind the diversification of several subspecies of North American cervids. We used genetics and the fossil record to study the phylogeography of three moose subspecies (Alces alces andersoni, A. a. gigas, and A. a. shirasi) in western North America. We sequenced the complete mitochondrial genome (16,341 base pairs; n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 77 publications
3
17
1
Order By: Relevance
“…We only detected low levels of inbreeding arising from long ROH (≥2 Mb), commonly caused by recent mating with relatives during bottlenecks [53,54]. This result is at odds with previous studies which identified limited mitochondrial and nuclear diversity in moose populations from Europe [21,28] and North America [27,56]. Moreover, evidence for a severe reduction in effective population size to less than 3% of their former size (down to N e~4 00), lasting for hundreds of generations and possibly dating back as early as the fifteenth century, has been previously reported in Swedish moose populations [21].…”
Section: Moose Genomic Diversitycontrasting
confidence: 99%
See 4 more Smart Citations
“…We only detected low levels of inbreeding arising from long ROH (≥2 Mb), commonly caused by recent mating with relatives during bottlenecks [53,54]. This result is at odds with previous studies which identified limited mitochondrial and nuclear diversity in moose populations from Europe [21,28] and North America [27,56]. Moreover, evidence for a severe reduction in effective population size to less than 3% of their former size (down to N e~4 00), lasting for hundreds of generations and possibly dating back as early as the fifteenth century, has been previously reported in Swedish moose populations [21].…”
Section: Moose Genomic Diversitycontrasting
confidence: 99%
“…While inbreeding was generally low, it is however worth noting that the two Rocky Mountain moose (A. a. shirasi) specimens had the largest inbreeding coefficients and the longest ROH (~4-5 Mb). This is consistent with these southernmost North American populations being founded from relatively few individuals after the declines of the late 1800s and with low gene flow from northern populations until the middle of the 20th century [27].…”
Section: Moose Genomic Diversitysupporting
confidence: 84%
See 3 more Smart Citations